The Bonus-Income Donation Norm - Michalis Drouvelis; Adam Isen; Benjamin M. Marx (Center for Economic Studies and ifo Institute (CESifo), 2019)
Can social norms affect fundamental patterns of behavior such as income effects? Studies of determinants of giving to charities and other individuals yield a wide range of income-effect estimates. We conduct two experiments to first test whether the effect of income on charitable giving depends on whether the income is earned and then test whether any difference in the effects by income source can be explained by social norms. Our first experiment induces random variation in both earned income and windfall bonuses and shows that only bonuses increases charitable donations. The second experiment uses an incentivized coordination game to investigate whether social norms can explain this donation pattern. Perceptions of what most people would consider a morally appropriate donation depend on the amount of income and whether it is a windfall. The norms elicited in the second experiment match the donation patterns in the first experiment both overall and across subject demographics, pointing to social norms as a key determinant of charitable giving.
Keywords: D01; D64; A13; 330; charitable; donation; warm glow; social preferences; income effect; experiment